PENGARUH PENGELOLAAN BELANJA DAERAH TERHADAP KINERJA UMKM DI KOTA KEDIRI - Wiwiek Andajani; I Gusti Gede Heru Marwanto (Equilibrium: Jurnal Penelitian Pendidikan dan Ekonomi, 2022)
Abstract  The Government of Kediri City received an award regarding regional government management in 2020 with a very high score of 3.4198. This award was given by the Ministry of Home Affairs. The award is expected to have a significant influence on increasing economic growth and community welfare in the Kediri city area. From BPS data, the economic growth and public welfare (Human Development Index/HDI) of the city of Kediri increased in 2018 – 2019. Nevertheless, in 2020 there was a decline in economic growth regardless of an increase in the HDI. The achievement proved a high commitment from the government of Kediri City in efforts to increase economic growth and community welfare through the allocative role of regional expenditures. The purpose of the research was to determine the effect of increasing local government spending on the performance of the Kediri City Government and to determine the performance factors of MSMEs that have a dominant influence in their contribution to increasing the rate of economic growth in Kediri City. Using quantitative research methods and the survey, the sample was determined intentionally, namely MSMEs that receive financial assistance/grants from the local government. The results of the analysis show that there was an effect of increasing regional spending on the performance of MSMEs. The main performances of MSMEs included increased sales growth, capital, annual additional workforce, market share, and marketing growth, as well as better operating profits. Keywords: Regional Expenditure; Performance; MSMEs; Management  Abstrak  Penghargaan yang diterima oleh Pemerintah Daerah Kota Kediri dari Kementrian Dalam Negeri pada tahun 2020 atas penyelenggaraan kegiatan Pemerintah Daerah dengan skor yang sangat tinggi, yaitu 3,4198. Penghargaan ini tentunya diharapkan memberikan pengaruh yang signifikan terhadap peningkatan pertumbuhan ekonomi dan kesejahteraan masyarakat. Dari data BPS, pertumbuhan ekonomi dan kesejahteraan masyarakat (IPM) kota Kediri mengalami peningkatan pada tahun 2018 – 2019. Akan tetapi, di tahun 2020 terjadi penurunan pertumbuhan ekonomi, meskipun IPM meningkat. Hal ini menunjukkan adanya komitmen yang tinggi dari pemerintah Kota Kediri dalam upaya meningkatkan pertumbuhan ekonomi dan kesejahteraan masyarakat melalui peran alokatif belanja daerahnya. Terkait hal ini, penelitian dilakukan dengan tujuan untuk mengetahui pengaruh peningkatan belanja daerah Pemerintah Kota Kediri terhadap kinerja UMKM dan untuk mengetahui faktor kinerja UMKM yang memberikan pengaruh dominan dalam kontribusinya pada peningkatan laju pertumbuhan ekonomi di Kota Kediri. Metode penelitian kuantitatif ini dilaksanakan melalui survey. Penentuan sampel dilakukan secara sengaja, yaitu umkm yang memperoleh bantuan dana/hibah dari pemerintah daerah. Hasil analisisnya menunjukkan adanya pengaruh peningkatan belanja daerah Pemerintah Kota Kediri terhadap kinerja UMKM. Adapun yang termasuk dalam kinerja utama UMKM, di antaranya adalah meningkatnya pertumbuhan penjualan, modal, penambahan tenaga kerja setiap tahun, pertumbuhan pangsa pasar dan pemasaran, serta keuntungan laba usaha yang semakin baik.Kata kunci: Belanja Daerah; Kinerja; UMKM; Pengelolaan